Critical Exploration and Updated Review on COVID-19 - Shahu, Prachi A. (Asian Journal of Pharmaceutics (AJP), 2023)
Coronaviruses (COVID-19) belong to a group of viruses that can harm the respiratory and digestive systems. Everyone is susceptible to respiratory infections, which depend on the illness and can last from a mild cold to more serious illnesses. There are two Middle Eastern Respiratory Syndrome Coronavirus (MERS-CoV) cases: Chronic obstructive pulmonary disease and MERS. An updated version of coronavirus, that is, novel coronavirus recently originated in human beings. Coronavirus is the unit thus named as a result of the means that they seem underneath a magnifier. The virus comprises a genetic material core of genetic material encased within a spikelike associate degree envelope. In Latin, the term corona refers to “corona.” Coronaviruses can spread from animals to people since they are an ailment that affects animals. MERS-CoV and SARS-CoV can transfer from cats and camels to humans, respectively. On December 31, 2019, a bunch of cases of respiratory illness of unidentified cause, within the town of the city, Hubei region in China, informed by the World Health Organization (WHO). All revealed inherited sequences of SARS-CoV-2 remote from human cases square measure analogous. In 2020, an antecedently unidentified latest virus was known, afterward called the 2019 novel coronavirus, and the section obtained from cases and studies of the virus’ biological science direct the reason for happening. The WHO recognized the existence of this novel coronavirus in the year 2020. It was named COVID-19 or Coronavirus Infectious Disease-2019. The illness caused by the virus, SARS-CoV-2, is known as COVID-19.